Real-Time Duct Prediction and Propagation Analysis Using Genetic Algorithm-Based RFC and Parabolic Equation Method - Heo, Jun; Jang, Doyoung; Choo, Hosung; Na, Dong Yeop; Bae Park, Yong (IEEE Access, 2025)
This paper proposes a real-time prediction of the duct using a refractivity from clutter (RFC) method based on genetic algorithm (GA) and the parabolic equation (PE) method. Three dates with duct formation are selected, and the refractivity calculated using atmospheric measurements is compared with the refractivity obtained through the GA-based RFC method. Additionally, using the PE method, the electromagnetic wave propagation for each refractivity is analyzed and compared. The atmospheric refractivity and propagation prediction results derived from the proposed process are validated to be similar to those of the measurements. The proposed method enables real-time duct prediction and propagation trend analysis at low altitudes using clutter signals.
Keywords: Atmospheric measurement; Atmospheric propagation; Atmospheric refractivity; Duct prediction; Electromagnetics; Parabolic equation method; Propagation analysis; Real- time; Real-time prediction; Refractivity from clutters; Duct prediction; genetic algorithm; parabolic equation method; propagation analysis; refractivity from clutter